Genetic characterization identifies bottom-of-sulcus dysplasia as an mTORopathy. (3rd November 2020) - Lee, Wei Shern; Stephenson, Sarah E.M.; Pope, Kate; Gillies, Greta; Maixner, Wirginia; Macdonald-Laurs, Emma; MacGregor, Duncan; D'Arcy, Colleen; Jackson, Graeme; Harvey, A. Simon; Leventer, Richard J.; Lockhart, Paul J.
Abstract : Objective: To determine the genetic basis of bottom-of-sulcus dysplasia (BOSD), which is a highly focal and epileptogenic cortical malformation in which the imaging, electrophysiologic, and pathologic abnormalities are maximal at the bottom of sulcus, tapering to a normal gyral crown. Methods: Targeted panel deep sequencing (>500×) was performed on paired blood and brain-derived genomic DNA from 20 operated patients with drug-resistant focal epilepsy and BOSD. Histopathology was assessed using immunohistochemistry. Results: Brain-specific pathogenic somatic variants were found in 6 patients and heterozygous pathogenic germline variants were found in 2. Somatic variants were identified in MTOR and germline variants were identified in DEPDC5 and NPRL3 . Two patients with somatic MTOR variants showed a mutation gradient, with higher mutation load at the bottom of sulcus compared to the gyral crown. Immunohistochemistry revealed an abundance of dysmorphic neurons and balloon cells in the bottom of sulcus but not in the gyral crown or adjacent gyri. Conclusions: BOSD is associated with mTOR pathway dysregulation and shares common genetic etiologies and pathogenic mechanisms with other forms of focal and hemispheric cortical dysplasia, suggesting these disorders are on a genetic continuum.